Integration of Non-Targeted Metabolomics and Targeted Quantitative Analysis to Elucidate the Synergistic Antidepressant Effect of Bupleurum Chinense DC-Paeonia Lactiflora Pall Herb Pair by Regulating Purine Metabolism - Chen, Jiajun; Li, Tian; Qin, Xuemei; Du, Guanhua; Zhou, Yuzhi (Frontiers in Pharmacology, 2022)
Graphical Abstract